Legal Aspect of Micro, Small, and Medium Business Partnership Agreements through Digital Platforms to Improve Community's Economy - Ilmih, Andi Aina; Zulkarnain, A. (JURNAL AKTA, 2025)
This research focuses on MSME Partnership Agreements through Digital Platforms to improve the community's economy. This research begins by analyzing arrangements related to MSME partnership agreements through digital platforms in Indonesia. Seeing that there are legal arrangements for partnership agreements, forms of MSME partnership agreements and adequate digital platforms, this encourages researchers to conduct in-depth studies. This research was conducted through a digital platform that is available electronically, with the aim of discovering the reality related to the form of MSME partnerships in Indonesia, especially MSMEs in the Semarang City area, then analyzing the legal arrangements regarding MSME partnership agreements and digital platforms, carried out using a descriptive analysis method. Data collection techniques through direct interviews and documentation. Data analysis used qualitative analysis methods with inductive and reflective logic then described systematically according to the problems studied. Based on the research that has been done, legal arrangements for MSME partnership agreements through digital platforms have not been specifically regulated in statutory provisions. Various laws and regulations that currently exist only regulate matters of a general nature, only mentioning the partnership pattern and the term business partnership for MSMEs. In addition, the legal aspects of the Partnership Agreement through the Digital Platform regarding the content and nature of the agreement are still limited. In practice, partnership agreements through digital platforms cause legal problems for their users, both MSME actors and consumers due to access restrictions and policies by digital platform service providers.